Intracavity Faraday modulation spectroscopy (INFAMOS): A tool for radical detection - Gianella, M; Pinto, T; Wu, X; Ritchie, G (AIP Publishing, 2017)
We present the INFAMOS technique, whereby optical feedback cavity-enhanced spectroscopy is coupled with Faraday modulation spectroscopy to greatly enhance the interaction path length of a laser beam with a paramagnetic sample in a magnetic field. We describe a first prototype based upon a cw quantum cascade laser targeting a selection of fundamental rovibrational Rbranch transitions of nitric oxide (1890 cm−1 ), consisting of a linear cavity (finesse F = 6300) and a water-cooled solenoid. We demonstrate a minimum detectable Verdet constant of Vmin = 4.7 × 10−14 rad cm−1 G −1 Hz−1/2 (at SNR = 1), corresponding to a single-pass rotation angle of 1.6 × 10−10 rad Hz−1/2 and a limit of detection of 0.21 ppbv Hz−1/2 NO.